THEORETICAL BACKGROUND IMPROVE THE RELIABILITY OF NUTRIENT REMOVAL FROM DOMESTIC WASTEWATER USING ACTIVATED THE REAGENT SOLUTION - , Т. А. (Municipal economy of cities (Technical science), 2013)
The influence of the activated coagulant solution on the degree of structural and mechanical hydration of aluminum hydroxide and changes in adhesion forces download contact clarifier advanced treatment of wastewater.